Intelligent traffic control system using fuzzy Logic / Shahrulnizar Mohamad Alias - Mohamad Alias, Shahrulnizar (2008)
This report paper is intended to document a report for EEE690 Project 2 Degree. It covers the results and also the progress report continued from the last semester work done. The implementation of an intelligent traffic light control system using fuzzy logic technology which capability of mimicking human intelligent for controlling traffic light. This is to replace and improve the performance of conventional fixed time traffic light control system. The inputs fuzzy variables are quantized constant signals and the output fuzz) variable is the length of time to extend in seconds. Software based on MATLAB has been developed to simulate an isolated traffic junction and implement to the hardware interfacing with using microcontroller PIC16F877A